Pembuatan Skala Konformitas untuk Anak yang Melakukan Pelanggaran Hukum - Widyastuti Widyastuti; Fitriah Gita Maharani; Erlita Auratul Ayun; Suriana Suriana; Dinda Ramadhani Lestari; Dewani Tenri Bali; Tri Anugrah Eni (HUMAN: South Asian Journal of Social Studies, 2022)
Abstract. The purpose of this study was to see the effect of conformity on the behavior of adolescents who are experiencing legal problems at the Center for Social Rehabilitation of Children requiring Special Attention (BRSAMPK) Toddopuli Makassar and at the Institute for Special Child Development (LPKA) Maros by taking a sample of 65 respondents by conducting a test. try to scale using random sampling technique. Based on population data from the Maros Child Special Development Institute (LPKA) archives for 2020-2021, it shows that there are 158 violations of the law committed by children. Data from the archives of the Toddopuli Makassar Social Rehabilitation Center for Children Requiring Special Attention (BRSAMPK) FOR 2020-2021 shows that there were 180 violations of the law. The results of the scale trial of 26 scale items, there are 10 items that fall, so that the remaining 16 items in the Item Discriminant Power test. The next test was carried out, namely the validity test, based on this the remaining 16 items were declared valid. And in the next test, namely the reliability test based on this, 16 items were declared reliable using the SPSS application and were appropriate to be used to determine the existence of conformity behavior in adolescents who violated the law. Thus the child is very dependent on friends or groups. The tendency of attachment in the group will increase with the increasing frequency of interaction among its members so that it will be followed by high and low conformity behavior towards children. The results of the scale trial sampling are that male adolescents are more likely to behave in conformity, at the age of 13-18 years is a period of transitional adolescence to seek to be themselves and education is also very influential on conformity behavior in adolescents. This is in accordance with the opinion of Santrock (2003) that boys do more anti-social behavior than girls.Keywords: Youth, Conformity, Violation of the law